The time course of postmatch physical impairments in professional soccer: A systematic review - Drayton, A. M.; Hamad, M. J.; Spyrou, K. (The Journal of Strength and Conditioning Research, 2025)
Professional soccer often requires players to compete every 72 hours (h), which can lead to notable fatigue and exercise-induced muscle damage. Knowledge of postmatch impairments of physical performance can support efforts to maintain optimal performance and minimize injury risk, alongside factors such as nutrition, training structure, and sleep. This review aimed to assess the effect of single soccer matches on measures of physical performance in professional players, investigating their response at different time points: immediately, 24, 48, and 72 hours postmatch. A literature search was conducted in November 2024 on the following databases: Medline (PubMed), Web of Science, and Scopus. A total of 13 studies were eligible and included in this review. Results show that even after 72 hours, professional players still experienced significant physical impairments. Although sprint, change of direction, and technical ability had all recovered by 72 hours, studies still observed significant impairments in vertical jump ability and hamstring strength, highlighting the complexity of postmatch fatigue. Nevertheless, variations in postmatch physical impairments were observed across studies, suggesting that many factors such as baseline physical fitness levels play a determining role in the duration of these impairments. Future research is needed in elite soccer populations to better understand the extent to which specific physical fitness measures (strength, aerobic fitness, power, etc.) influence postmatch physical impairments. Nevertheless, practitioners should be aware of the varied individual recovery profiles observed in professional players, to optimize player readiness and reduce injury risk.